Plant Electrophysiology Theory and Methods - Volkov, Alexander G. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
As a pioneering work on plant electrophysiology, this exciting reference compiles new findings from the work of internationally renowned experts in the fields of electrophysiology, bio-electrochemistry, biophysics, signal transduction, phloem transport, tropisms, ion channels, plant electrochemistry, and membrane transport. The book starts with a historical introduction to plant electrophysiology, followed by two distinct parts. The first one deals with methods in plant electrophysiology, including, amongst others, measuring membrane potentials and ion fluxes, path-clamp technique, and electrochemical sensors. The second part covers experimental results and their theoretical interpretation.